2022
DOI: 10.3390/pathogens11091029
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus among Pregnant Women and Neonates in Saudi Arabia: A Systemic Review

Abstract: Sepsis caused by Group B Streptococcus (GBS) continues to cause mortality and morbidity in newborns, especially in developing countries. Bacterial sepsis in newborns varies nationally and even within countries. Developing countries have reported 34 deaths per 1000 live births compared to 5 in developed countries. This systemic review aimed to assess the prevalence of GBS colonization among pregnant women and the incidence of neonatal GBS sepsis in Saudi Arabia. A literature search of PubMed, MEDLINE Ovid, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…12 Locally, it was also observed that GBS colonization prevalence was higher among women in the cities Riyadh )27.6%( and Jeddah )31.6%(, Saudi Arabia. 5 Studies have reported varying rates of maternal GBS colonization in Saudi Arabia, ranging from 13.4-31%. [13][14][15] However, a study by Ahmad et al 16 reported a prevalence of 2.1% for maternal GBS colonization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Locally, it was also observed that GBS colonization prevalence was higher among women in the cities Riyadh )27.6%( and Jeddah )31.6%(, Saudi Arabia. 5 Studies have reported varying rates of maternal GBS colonization in Saudi Arabia, ranging from 13.4-31%. [13][14][15] However, a study by Ahmad et al 16 reported a prevalence of 2.1% for maternal GBS colonization.…”
Section: Methodsmentioning
confidence: 99%
“… 3 The global average prevalence of colonized women with GBS is 18% ranging from a high prevalence in the Caribbean of 35% to a much lower prevalence in Southern Asia at 13%, and Eastern Asia at 11%, while locally in Saudi Arabia the GBS colonization prevalence among pregnant women ranged from 2.1-32.8%. 4 , 5 So neonates are 29 times more likely to experience early-onset disease (EOD), although only 1-2% will experience invasive GBS infection. Risk factors for EOD include positive GBS colonization, preterm labor before the 37th week of gestation, prolonged premature rupture of membranes lasting more than 18 hours, and higher body temperature during delivery.…”
mentioning
confidence: 99%
See 1 more Smart Citation